Staatlichkeit und politisches Handeln in der römischen Kaiserzeit - Wiemer, Hans-Ulrich (Millennium-Studien / Millennium Studies, 2012)
This collected volume contributes to the discussion among ancient historians of the character and form of political action in Imperial Rome. It concentrates on the East of the Imperium Romanum for the whole duration of the Imperial Era, including Late Antiquity. Using concrete examples, the individual papers explore the question of how much latitude and freedom of action was exercised by the emperors - and by other authorities, such as governors and cities - and whether their actions display a political strategy which went beyond merely reacting to impulses from their subjects and subordinates.